2018
DOI: 10.1016/j.yhbeh.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid effects of ovarian hormones in dorsal striatum and nucleus accumbens

Abstract: Contribution to Special Issue on Fast effects of steroids. Estradiol and progesterone rapidly induce changes in dopaminergic signaling within the dorsal striatum and nucleus accumbens of female rats. In ovariectomized females, estradiol rapidly enhances dopamine release and modulates binding of dopamine receptors. Progesterone further potentiates the effect of estradiol on dopamine release. The effects of both estradiol and progesterone are time course dependent, with increases in dopamine release immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 104 publications
2
127
0
Order By: Relevance
“…Three subjects dropped out of the study due to illness or personal reasons, two after the initial baseline session and one after the first fMRI session. Only males were included, as female sex hormones fluctuate during menstrual cycle which may affect DA signaling (Almey, Milner, & Brake, 2015;Yoest, Quigley, & Becker, 2018). Participants were recruited online and included mainly university students.…”
Section: Participantsmentioning
confidence: 99%
“…Three subjects dropped out of the study due to illness or personal reasons, two after the initial baseline session and one after the first fMRI session. Only males were included, as female sex hormones fluctuate during menstrual cycle which may affect DA signaling (Almey, Milner, & Brake, 2015;Yoest, Quigley, & Becker, 2018). Participants were recruited online and included mainly university students.…”
Section: Participantsmentioning
confidence: 99%
“…Within the dorsal striatum, oestradiol acutely enhances dopamine release in females but not in males (Cummings et al ., ; Shams et al ., ). A substantial body of work has demonstrated that oestradiol acts directly on GABAergic striatal tissue to disinhibit dopaminergic terminals and promote dopamine release within the striatum (Yoest et al ., ). However, while the effects of oestradiol in dorsal striatum have been well established, studies on the rapid effects of oestradiol on dopamine release within the nucleus accumbens (NAc) have produced mixed results.…”
Section: Introductionmentioning
confidence: 97%
“…The mesocorticolimbic dopamine (DA) system is critical for the rewarding and reinforcing effects of ethanol (Gonzales et al, 2004;Lovinger and Alvarez, 2017). E2 has potent modulatory effects on this system (Yoest et al, 2018a). For example, E2 enhances cocaine-, amphetamine-, and potassium-stimulated DA release in the striatum of rats and mice (Becker, 1990a, b;Thompson and Moss, 1994;Tobiansky et al, 2016;Yoest et al, 2018b), and potentiates ethanol-stimulated DA release in the prefrontal cortex of female rats (Dazzi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%